Interface enhanced flame-retardant polylactic acid plant fiber composite material and preparation method and application thereof

CN122878596APending Publication Date: 2026-10-09CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611088894.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-22
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0006]为了解决上述技术问题,本发明的目的是提供一种界面增强阻燃聚乳酸植物纤维复合材料及其制备方法和应用,以解决现有PLA/植物纤维复合材料中植物纤维与PLA基体界面结合差、载荷传递效率低、材料易燃以及阻燃剂直接添加易导致团聚和力学性能下降的问题

Benefits of technology

1、本发明以聚乳酸为基体、植物纤维为生物质增强相,先采用NaOH水体系对植物纤维进行温和活化,再将聚D-乳酸(PDLA)预先锚定于植物纤维表面以构建PLA同源界面层,从而提高界面结合强度。进一步,将六苯氧基环三磷腈(HPCTP)通过溶液沉积方式富集于植物纤维/PLA界面区域,形成兼具载荷传递与P/N阻燃成炭功能的界面层,从而实现力学性能和阻燃性能的协同提升。该方法能够改善传统PLA/植物纤维复合材料界面相容性差、力学性能不稳定及易燃的问题,并减少阻燃剂直接共混导致的团聚和力学性能下降。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122878596A_ABST
    Figure CN122878596A_ABST
Patent Text Reader

Abstract

The application discloses an interface-enhanced flame-retardant polylactic acid plant fiber composite material and a preparation method and application thereof, and relates to the technical field of bio-based composite material preparation.The method comprises the following steps: drying plant fibers, adding NaOH solution; adding a poly-D-lactic acid (PDLA) solution to obtain PDLA modified plant fibers; adding a flame retardant into a solvent and adding the PDLA modified plant fibers; and melt blending polylactic acid, shaping, and obtaining the product.The application unifies "interface enhancement" and "flame-retardant functionalization" on the same interface, so that the plant fiber / PLA interface simultaneously bears load transmission, carbon skeleton formation and P / N flame-retardant functions, thereby realizing the synergistic improvement of mechanical properties and flame-retardant properties.The application solves the problems of poor interface bonding between plant fibers and a PLA matrix, low load transmission efficiency, flammability of the material, and easy agglomeration and mechanical property reduction caused by direct addition of a flame retardant in the existing PLA / plant fiber composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] This invention relates to the field of bio-based composite material preparation technology, specifically to an interface-reinforced flame-retardant polylactic acid plant fiber composite material, its preparation method, and its application. Background Technology

[0003] Polylactic acid (PLA) is derived from renewable resources and is characterized by its biodegradability, low carbon footprint, and good processability, making it suitable for use in bio-based composites. Plant fibers offer advantages such as abundant availability, high specific strength, low density, and renewability. Adding plant fibers to PLA can reduce material costs and improve rigidity. However, plant fibers contain a large number of hydroxyl groups on their surface, making them hydrophilic, while PLA is relatively hydrophobic. Direct composites of the two exhibit poor interfacial compatibility, often leading to problems such as fiber agglomeration, interfacial porosity, fiber pull-out, and insufficient stress transfer. This results in limited improvement in tensile strength, flexural strength, and impact performance, and may even lead to a decline in mechanical properties.

[0004] To address the interface issues in PLA / plant fiber composites, silane coupling agent treatment, dopamine coating, tannic acid coating, or other surface modification methods are commonly employed. While these methods can improve interfacial bonding to some extent, they still suffer from drawbacks such as demanding processing conditions, potential damage to plant fibers, insufficient homology between the interfacial layer and the PLA matrix, unstable modification effects, or complex processes. Ordinary coupling agent treatment may lead to interface inhomogeneity due to improper control of hydrolysis and condensation. Furthermore, both PLA and plant fibers are flammable materials. PLA easily melts, drips, and releases combustible volatiles during combustion, while plant fibers are also prone to pyrolysis and combustion upon heating. The fiber structure also exhibits wicking effects, with the resin melting due to the fiber's good thermal conductivity and rapidly adsorbing through capillary action, igniting rapidly under external flame. Traditional flame retardant methods typically involve directly adding flame retardants to the PLA matrix, such as ammonium polyphosphate, phytates, metal hydroxides, or organophosphorus flame retardants. While these methods can improve flame retardant performance, they often result in high flame retardant dosages, uneven dispersion, increased hygroscopicity, interfacial damage, and decreased mechanical properties. To overcome this shortcoming, an interfacial flame retardant method has been proposed, which involves grafting flame retardant groups onto the fiber surface. These flame retardant groups can dilute the fuel. The interface is the key factor determining the mechanical properties of composite materials. Grafting organic flame retardant groups onto the fiber surface can improve the compatibility between the fiber and the resin, and it is expected to improve both flame retardancy and mechanical properties simultaneously.

[0005] However, in existing technologies, interface reinforcement and flame retardant modification are often independent: interface reinforcement mainly addresses mechanical issues, while direct blending of flame retardants mainly addresses combustion issues, lacking a synergistic design for the plant fiber / PLA interface. When flame retardants are randomly distributed in the PLA matrix, it is difficult to fully utilize the char-forming skeleton effect of plant fibers, and defects are easily formed in the matrix. Therefore, there is an urgent need to develop an interface synergistic construction method that can simultaneously improve the PLA / plant fiber interface bonding, enhance flame retardant properties, and maintain mechanical properties. Summary of the Invention

[0006] To address the aforementioned technical problems, the present invention aims to provide an interface-reinforced flame-retardant polylactic acid plant fiber composite material, its preparation method, and its application, thereby solving the problems of poor interfacial bonding between plant fibers and the PLA matrix, low load transfer efficiency, flammability of the material, and the tendency of direct addition of flame retardants to lead to agglomeration and decreased mechanical properties in existing PLA / plant fiber composite materials.

[0007] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A method for preparing an interface-reinforced flame-retardant polylactic acid plant fiber composite material is provided, comprising the following steps: (1) Dry the plant fiber to obtain dried plant fiber, add NaOH solution, heat treat, then filter, wash and dry to obtain NaOH activated plant fiber; (2) Dissolve poly-D-lactic acid in a solvent, add the NaOH activated plant fiber obtained in step (1), stir, then evaporate the solvent and dry to obtain PDLA modified plant fiber; (3) Add flame retardant to solvent, add PDLA modified plant fiber obtained in step (2), stir, then evaporate solvent and dry to obtain flame retardant functionalized plant fiber; (4) The flame-retardant functionalized plant fiber obtained in step (3) is melt-blended with polylactic acid and molded to obtain an interface-reinforced flame-retardant polylactic acid plant fiber composite material.

[0008] The beneficial effects of this invention are as follows: NaOH solution can gently activate the surface of plant fibers, remove some surface wax, impurities and loose components, increase surface roughness and hydroxyl groups, and improve the wetting and penetration of subsequent PDLA solution on the surface of plant fibers.

[0009] The interface enrichment layer between PDLA and plant fibers is mainly formed through hydrogen bonds, dipole interactions, van der Waals interactions between hydroxyl groups on the plant fiber surface and PDLA ester / carbonyl groups, as well as physical intercalation on rough surfaces. PDLA does not necessarily exist in a covalent grafting manner, but rather achieves preferential anchoring on the plant fiber surface through pre-coating.

[0010] During the melt composite process, the PDLA on the surface of the plant fiber and the PLLA segments in the PLA matrix undergo homologous compatibility and segment entanglement, and are expected to form a stereocomposite crystalline structure at the interface, thereby forming a physical anchoring point and improving the load transfer efficiency from the PLA matrix to the plant fiber.

[0011] The flame retardant is located near the plant fiber / PLA interface through solution deposition and interfacial enrichment. During combustion, the P / N structure in the flame retardant promotes the dehydration of PLA and plant fibers into char. The plant fibers, as the char skeleton, help form a protective char layer containing P / N, inhibiting heat transfer, oxygen diffusion, and the release of combustible volatiles.

[0012] Based on the above technical solution, the present invention can be further improved as follows: Furthermore, in step (1), the plant fiber is dried at 80°C for 12 hours.

[0013] Furthermore, in step (1), the plant fiber is bamboo fiber, bamboo powder, wood powder, hemp fiber or straw fiber.

[0014] Furthermore, in step (1), the plant fiber is bamboo fiber.

[0015] Furthermore, in step (1), the concentration of the NaOH solution is 2-6 g / L.

[0016] Furthermore, in step (1), the concentration of the NaOH solution is 5 g / L.

[0017] Furthermore, in step (1), lactic acid, acetic acid or citric acid are added to the NaOH solution as an auxiliary agent.

[0018] Furthermore, in step (1), the mixture is stirred at 40-50℃ for 0.5-2 hours to complete the heat treatment process.

[0019] Furthermore, in step (1), the mixture is stirred at 45°C for 0.5 h to complete the heat treatment process.

[0020] Furthermore, in step (1), after washing, the product is dried at 80°C for 12 hours.

[0021] Furthermore, in step (2), the solvent is ethyl lactate and / or ethyl acetate.

[0022] Furthermore, in step (2), the mass-volume ratio of poly-D-lactic acid to solvent is 5g:400mL.

[0023] Furthermore, in step (2), the mixture is stirred for 2 hours.

[0024] Furthermore, in step (2), the product is dried at 60°C for 4 hours and then vacuum dried at 80°C for 12 hours.

[0025] Furthermore, in step (3), the solvent is a mixture of ethyl lactate and ethyl acetate.

[0026] Furthermore, in step (3), the mass-volume ratio of flame retardant to solvent is 10g:300mL.

[0027] Furthermore, in step (3), the flame retardant is hexaphenoxycyclotriphosphazene, phenoxycyclotriphosphazene, polyphosphazene, or a flame retardant containing P / N cyclotriphosphazene.

[0028] Furthermore, in step (3), the mixture is stirred for 2 hours.

[0029] Furthermore, in step (4), melt blending is carried out at 175°C.

[0030] In step (4), the mass ratio of flame retardant functionalized plant fiber to polylactic acid is (100-120): (200-230).

[0031] Furthermore, in step (4), the mass ratio of flame retardant functionalized plant fiber to polylactic acid is 115:216.3.

[0032] This invention also provides an interface-reinforced flame-retardant polylactic acid plant fiber composite material prepared by the above method. The present invention also provides the application of the above-mentioned interface-reinforced flame-retardant polylactic acid plant fiber composite material in interior decorative panels, furniture parts, low-load structural components, electronic and electrical appliance housings, or low-carbon flame-retardant components for public spaces.

[0033] The present invention has the following beneficial effects: 1. This invention uses polylactic acid (PLA) as the matrix and plant fiber as the biomass reinforcing phase. First, the plant fiber is gently activated using a NaOH aqueous system. Then, poly-D-lactic acid (PDLA) is pre-anchored to the surface of the plant fiber to construct a PLA homologous interface layer, thereby improving the interfacial bonding strength. Furthermore, hexaphenoxycyclotriphosphazene (HPCTP) is enriched in the plant fiber / PLA interface region through solution deposition, forming an interface layer that combines load transfer and P / N flame retardant charring functions, thus achieving a synergistic improvement in mechanical and flame retardant properties. This method can improve the problems of poor interfacial compatibility, unstable mechanical properties, and flammability in traditional PLA / plant fiber composites, and reduce the agglomeration and mechanical property degradation caused by direct blending of flame retardants.

[0034] 2. Compared with untreated PLA / plant fiber composites, this invention can improve the wetting and coating degree of PLA on plant fibers, reduce fiber pull-out, interfacial debonding, and porosity defects, and improve the comprehensive mechanical properties of the composite material, such as tensile, bending, and impact properties. Compared with direct blending of PDLA, this invention pre-anchors PDLA to the surface of plant fibers, which can improve the utilization efficiency of PDLA in the plant fiber / PLA interface region, allowing PDLA to more effectively exert its homologous compatibility and interfacial physical anchoring effects. Compared with direct blending of flame retardants, this invention enriches HPCTP near the plant fiber / PLA interface, which is beneficial for utilizing the char-forming skeleton of plant fibers and the P / N flame-retardant effect of HPCTP to form an interfacial char layer, thereby improving the limiting oxygen index, vertical burning performance, and cone calorimetric properties, and reducing the adverse effects of flame retardant agglomeration on mechanical properties.

[0035] 3. This invention uses a relatively green processing system such as NaOH, ethyl lactate and ethyl acetate. The process conditions are mild and it is suitable for conventional polymer processing methods such as mixing, twin-screw extrusion, hot pressing and injection molding. It has good potential for practical application.

[0036] 4. This invention does not simply involve traditional alkali treatment or coupling agent treatment of plant fibers. Instead, it constructs a PLA homologous interface layer through gentle activation with NaOH and surface anchoring of PDLA, transforming the plant fiber surface from a hydrophilic fiber interface to a polylactic acid (PLA) interface more compatible with the PLA matrix. This invention introduces the HPCTP flame retardant into the plant fiber / PLA interface region via solution deposition, rather than simply adding it directly to the PLA matrix. This improves the effective utilization rate of the flame retardant at the interface and reduces agglomeration and mechanical loss. This invention unifies "interface reinforcement" and "flame retardant functionalization" on the same interface, enabling the plant fiber / PLA interface to simultaneously undertake load transfer, char-forming skeleton, and P / N flame retardant functions, thereby achieving a synergistic improvement in both mechanical and flame retardant properties.

[0037] 5. This invention is applicable to the high-value utilization of plant fibers and the preparation of bio-based flame-retardant composite materials, and can be used in the fields of interior decorative panels, furniture parts, low-load structural components, electronic and electrical appliance housings, or low-carbon flame-retardant components for public spaces. Attached Figure Description

[0038] Figure 1 The tensile strength properties of the materials obtained in Examples 1-2 and Comparative Examples 1-4 are shown in the diagram. Figure 2 The diagram shows the flexural strength properties of the materials obtained in Examples 1-2 and Comparative Examples 1-4. Figure 3 The impact strength properties of the materials obtained in Examples 1-2 and Comparative Examples 1-4 are shown in the diagram. Figure 4This is a comparison diagram of the combustion of the materials prepared in Example 1 and Example 2. Detailed Implementation

[0039] The principles and features of the present invention are described below with reference to the accompanying drawings. The examples given are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified in the examples, conventional conditions or conditions recommended by the manufacturer should be followed. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0040] Example 1: A flame-retardant polylactic acid plant fiber composite material with interface reinforcement is prepared by the following steps: (1) 100g of bamboo fiber was dried at 80℃ for 12h to obtain dried bamboo fiber. NaOH solution (5g of NaOH and 1000mL of deionized water) was added and stirred at 45℃ for 0.5h. Then it was filtered, washed with deionized water, and then dried at 80℃ for 12h to obtain NaOH activated bamboo fiber. (2) Add 5g of poly-D-lactic acid to 300mL of ethyl lactate, stir and dissolve at 70℃ for 4h, cool down to 45℃, add 100mL of ethyl acetate, add the NaOH activated bamboo fiber obtained in step (1), stir for 2h, then evaporate the solvent, dry at 60℃ for 4h, and vacuum dry at 80℃ for 12h to obtain PDLA modified bamboo fiber; (3) Add 10g of hexaphenoxycyclotriphosphazene (HPCTP) to 300mL of organic solvent (ethyl lactate and ethyl acetate in a volume ratio of 1:1), stir at 43℃ for 1h to dissolve or uniformly disperse it, add the PDLA-modified bamboo fiber obtained in step (2), stir for 2h to allow HPCTP to deposit and accumulate at the bamboo fiber / PDLA interface, then slowly evaporate the solvent under ventilation conditions, dry at 60℃ for 4h, and vacuum dry at 80℃ for 12h to obtain HPCTP-functionalized bamboo fiber. (4) Add 115g of HPCTP functionalized bamboo fiber obtained in step (3) and 216.3g of polylactic acid to a twin-screw extruder, melt blend at 175°C, and then hot press and extrusion to form an interface-reinforced flame-retardant polylactic acid plant fiber composite material (denoted as HPCTP@PDLA@BF / PLA).

[0041] In this embodiment, HPCTP is enriched near the bamboo fiber / PLA interface. During combustion, the P / N structure of HPCTP promotes the synergistic formation of char by PLA and bamboo fiber. The bamboo fiber provides the char layer skeleton, and the interfacial char layer blocks the release of heat, oxygen, and combustible gases, thereby improving flame retardant performance and maintaining good mechanical properties.

[0042] Example 2: A polylactic acid plant fiber composite material, the preparation method of which includes the following steps: (1) 100g of bamboo fiber was dried at 80℃ for 12h to obtain dried bamboo fiber. NaOH solution (5g of NaOH and 1000mL of deionized water) was added and stirred at 45℃ for 0.5h. Then it was filtered, washed with deionized water, and then dried at 80℃ for 12h to obtain NaOH activated bamboo fiber. (2) Add 5g of poly-D-lactic acid to 300mL of ethyl lactate, stir and dissolve at 70℃ for 4h, cool down to 45℃, add 100mL of ethyl acetate, add the NaOH activated bamboo fiber obtained in step (1), stir for 2h, then evaporate the solvent, dry at 60℃ for 4h, and vacuum dry at 80℃ for 12h to obtain PDLA modified bamboo fiber; (3) Add 105g of PDLA-modified bamboo fiber obtained in step (2) and 226.3g of polylactic acid (pre-dried at 60°C for 12h) to a twin-screw extruder, melt blend at 175°C and 55rpm, then preheat at 175°C for 20min, hot press at 10MPa for 10min, and cold press to shape to obtain polylactic acid plant fiber composite material (denoted as PDLA@BF / PLA).

[0043] In this embodiment, PDLA is enriched on the surface of bamboo fiber through hydrogen bonding, solution deposition and physical intercalation, which can reduce fiber pull-out and interfacial pores and improve the mechanical properties of composite materials.

[0044] Example 2 was used to verify the enhancing effect of the polylactic acid homologous interface pre-anchored by PDLA on the bamboo fiber surface on the mechanical properties of the composite material. This example did not introduce HPCTP to eliminate the influence of flame retardants on mechanical properties. The improvement effect of PDLA modification on the bamboo fiber / PLA interface bonding, load transfer efficiency, and overall mechanical properties was evaluated by comparing it with Comparative Example 1 (without a PDLA homologous interface) and Comparative Example 2 (with direct melt blending of PDLA).

[0045] This embodiment serves as a verification group for the homologous interface enhancement, primarily used to demonstrate that pre-anchoring PDLA to the surface of bamboo fiber can effectively improve the interfacial bonding between bamboo fiber and PLA matrix, and that its mechanical enhancement effect is superior to that of direct melt blending of PDLA.

[0046] Comparative Example 1: A polylactic acid plant fiber composite material, the preparation method of which includes the following steps: Without steps (2) and (3), the rest is the same as in Example 1, and polylactic acid plant fiber composite material (denoted as untreated BF / PLA) is obtained.

[0047] Comparative Example 2: A polylactic acid plant fiber composite material, the preparation method of which includes the following steps: Weigh 100g of bamboo fiber, 5g of PDLA and 228.3g of PLA. After processing the bamboo fiber according to step (1) in Example 1, directly melt blend it to obtain polylactic acid plant fiber composite material (denoted as PDLA, BF / PLA blend).

[0048] Comparative Example 3: A polylactic acid plant fiber composite material, the preparation method of which includes the following steps: Weigh 100g of bamboo fiber, 10g of HPCTP and 228.3g of PLA. After processing the bamboo fiber according to step (1) in Example 1, directly melt blend it to obtain polylactic acid plant fiber composite material (referred to as HPCTP, BF / PLA blend).

[0049] Comparative Example 4: A polylactic acid plant fiber composite material, the preparation method of which includes the following steps: Weigh 100g of bamboo fiber, 5g of PDLA, 10g of HPCTP and 228.3g of PLA. After processing the bamboo fiber according to step (1) in Example 1, directly melt-blend it to obtain polylactic acid plant fiber composite material (denoted as PDLA, HPCTP, BF / PLA blend).

[0050] Test case I. The composite materials obtained in Examples 1 and 2, and Comparative Examples 1, 2, 3, and 4 were tested for tensile strength, flexural strength, and impact strength. The specific testing methods were as follows: tensile strength was tested according to GB / T 1040.2—2022 "Determination of tensile properties of plastics—Part 2: Test conditions for molded and extruded plastics"; flexural strength was tested using the three-point bending method according to GB / T 9341—2008 "Determination of flexural properties of plastics"; and impact strength was tested according to GB / T 1043.1—2008 "Determination of impact properties of simply supported beams of plastics—Part 1: Non-instrumental impact testing". At least five parallel samples were set for each group, and the arithmetic mean of the test results was taken. The results are shown in […]. Figure 1-3 .

[0051] Depend on Figure 1-3It can be seen that the tensile strength, flexural strength, and impact strength of the untreated BF / PLA composite material in Comparative Example 1 were 18.4 MPa, 39.1 MPa, and 9.4 kJ / m², respectively. After surface modification with PDLA, the tensile strength, flexural strength, and impact strength of the PDLA@BF / PLA composite material prepared in Example 2 increased to 32.9 MPa, 58.7 MPa, and 11.7 kJ / m², respectively, which were 78.8%, 50.1%, and 24.4% higher than those of the untreated BF / PLA in Comparative Example 1; and 29.5%, 24.3%, and 15.8% higher than those of Comparative Example 2, which was prepared by direct melt blending of PDLA, BF, and PLA. This indicates that pre-anchoring PDLA to the surface of bamboo fiber is more beneficial than directly adding PDLA to the composite system for melt blending in order to improve the interfacial bonding between bamboo fiber and PLA, promote stress transfer, reduce interfacial debonding and fiber pull-out, thereby improving the comprehensive mechanical properties of the composite material.

[0052] The tensile strength, flexural strength, and impact strength of the HPCTP@PDLA@BF / PLA composite material prepared in Example 1 were 30.7 MPa, 54.6 MPa, and 13.7 kJ / m², respectively, representing increases of 66.8%, 39.6%, and 45.7% compared to the untreated BF / PLA in Comparative Example 1. Compared to Comparative Example 4, prepared by direct melt blending of PDLA, HPCTP, BF, and PLA, these values ​​were increases of 52.0%, 34.8%, and 17.1%, respectively. Compared to Example 2, the tensile strength, flexural strength, and impact strength of Example 1 decreased by 7.2%, 7.5%, and 17.1%, respectively. In contrast, the tensile strength, flexural strength, and impact strength of the composite material prepared by direct melt blending of HPCTP, BF, and PLA were 14.3 MPa, 38.4 MPa, and 6.3 kJ / m², respectively. This demonstrates that pre-depositing and enriching HPCTP in PDLA and anchoring it in the interface region of bamboo fiber can mitigate the uneven dispersion and interface defects caused by direct blending of HPCTP, while maintaining high tensile strength, flexural strength, and impact performance.

[0053] II. The composite materials obtained in Examples 1 and 2 were subjected to combustion performance testing. The specific testing method was as follows: a vertical combustion test was conducted according to GB / T 2408—2021 "Determination of Combustion Performance of Plastics - Horizontal and Vertical Methods". Samples of uniform size and thickness were vertically fixed, and a flame was applied to the lower end of the sample for 10 seconds. After removing the flame source, the afterflame, molten dripping, and filamentous tailing phenomena were recorded. After the flame extinguished, the flame was applied again for 10 seconds, and the afterflame, molten dripping, and filamentous tailing phenomena were recorded a second time. After the test, the samples were cooled to room temperature, and their combustion area and char morphology were observed and photographed. At least five parallel samples were set up for each group. The results are shown below. Figure 4 ( Figure 4In the middle, from left to right, are those with HPCTP added and those without HPCTP added.

[0054] Depend on Figure 4 It was found that the PDLA@BF / PLA composite material without HPCTP showed significant melt shrinkage and melt accumulation after combustion, with poor structural integrity at the combustion end. During combustion, the continuous channels formed by bamboo fibers may have generated a wick effect, promoting the migration of PLA melt and combustible pyrolysis products along the fiber direction into the combustion zone. In contrast, the HPCTP@PDLA@BF / PLA composite material with added HPCTP formed a more continuous and complete charred residual structure in the combustion zone, with a relatively dense char surface, and melt flow and dripping were somewhat suppressed. This indicates that the introduction of HPCTP is beneficial for promoting the condensation of the composite material into char, improving the structural integrity and thermal stability of the char layer, thereby enhancing the barrier effect of the char layer on the transfer of heat, oxygen, and combustible volatile products, and improving the combustion performance of the bamboo fiber / PLA composite material.

[0055] The tensile and flexural strengths of Example 1 and Example 2 are similar, and the impact strength of Example 1 is improved. This indicates that the construction of the HPCTP flame-retardant functional layer did not significantly disrupt the continuity of the PDLA homologous interface layer and the interfacial bonding state. The composite material still maintains a high load transfer capacity, achieving a synergy between the introduction of flame-retardant function and the maintenance of interface reinforcement effect.

[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for preparing an interface-reinforced flame-retardant polylactic acid plant fiber composite material, characterized in that, Includes the following steps: (1) Dry the plant fiber to obtain dried plant fiber, add NaOH solution, heat treat, then filter, wash and dry to obtain NaOH activated plant fiber; (2) Dissolve poly-D-lactic acid in a solvent, add the NaOH activated plant fiber obtained in step (1), stir, then evaporate the solvent and dry to obtain PDLA modified plant fiber; (3) Add flame retardant to solvent, add PDLA modified plant fiber obtained in step (2), stir, then evaporate solvent and dry to obtain flame retardant functionalized plant fiber; (4) The flame retardant functionalized plant fiber obtained in step (3) is melt-blended with polylactic acid and molded to obtain an interface-reinforced flame retardant polylactic acid plant fiber composite material.

2. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (1), the plant fiber is dried at 80°C for 12 hours.

3. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (1), the plant fiber is bamboo fiber, bamboo powder, wood powder, hemp fiber or straw fiber.

4. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (1), the mixture is stirred at 40-50℃ for 0.5-2 hours to complete the heat treatment process.

5. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (2), the solvent is ethyl lactate and / or ethyl acetate; in step (3), the solvent is a mixture of ethyl lactate and ethyl acetate.

6. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (3), the flame retardant is hexaphenoxycyclotriphosphazene, phenoxycyclotriphosphazene, polyphosphazene or a flame retardant containing P / N cyclotriphosphazene.

7. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (4), melt blending is carried out at 175°C.

8. The method for preparing the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 1, characterized in that, In step (4), the mass ratio of flame retardant functionalized plant fiber to polylactic acid is (100-120): (200-230).

9. The interface-reinforced flame-retardant polylactic acid plant fiber composite material prepared by the method of any one of claims 1-8.

10. The application of the interface-reinforced flame-retardant polylactic acid plant fiber composite material according to claim 9 in interior decorative panels, furniture components, low-load structural parts, electronic and electrical appliance housings, or low-carbon flame-retardant components for public spaces.